Referral Patterns from Primary Care to Referral Care by ICD-10 Codes in Indonesia: Cross-Sectional Analysis of National Claims Data (2017–2024) - Ayu, Della Dwi; Hasibuan, Syarif Rahman; Pradnyani, Putu Erma; Widyasanti, Nisrina (UI Scholars Hub, 2026)
Primary health care (PHC) facilities serve as gatekeepers within Indonesia’s tiered health system. However, PHC referral patterns to hospitals still show substantial variation and remain insufficiently characterized by disease groupings based on the International Classification of Diseases, 10th Revision (ICD-10). This study aimed to identify the most frequently referred diagnoses from PHC to secondary or tertiary care facilities and to determine the participant characteristics associated with referrals. This observational study employed a cross-sectional design using secondary data from the National Health Insurance (Jaminan Kesehatan Nasional – JKN) claims database for the period 2017–2024. The unit of analysis was each patient visit to a PHC facility. The outcome variable was referral status (referred vs. not referred), with ICD-10 diagnostic codes as the main independent variable, while age and sex were covariates. Descriptive and inferential analyses, including binary logistic regression, were conducted to identify factors associated with referral likelihood. Of 1.2 billion visit episodes, 14% resulted in referrals to higher-level facilities. The most frequent diagnoses were classified under ICD-10 Code J (respiratory system diseases, 21.5%), yet referrals were most common among cases under Code C (neoplasms). Referrals were also more frequent among older adults and male patients.